2022
DOI: 10.1155/2022/6533243
|View full text |Cite|
|
Sign up to set email alerts
|

College Physical Education Flipped Classroom Teaching Based on Multimedia Network Data Fusion

Abstract: In the Internet age, the challenge to traditional physical education classroom teaching has also reached its peak. Traditional physical education teaching has little effect on students. The proposal of flipped classroom can be said to greatly improve the dilemma of traditional physical education classroom teaching. This article is aimed at studying the exploration of flipped classroom teaching in college physical education. For this reason, this paper proposes a data fusion method based on multimedia network t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…Related studies have shown that "MOOC+ flipped classroom" teaching can help improve students' performance in practical Schematic diagram of changes in self-regulated learning ability between the experimental group and the control group before and after the intervention. Hu et al 10.3389/fpsyg.2023.1060257 Frontiers in Psychology 10 frontiersin.org courses (Tang et al, 2018;Wang et al, 2018), and students are more proficient in physical skills with flipped classroom teaching in college sports (Zhao, 2022). Moreover, flipped classroom teaching in college sports basketball classes can improve students' professional basketball skills, which is consistent with the results of this study (Wang, 2021).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Related studies have shown that "MOOC+ flipped classroom" teaching can help improve students' performance in practical Schematic diagram of changes in self-regulated learning ability between the experimental group and the control group before and after the intervention. Hu et al 10.3389/fpsyg.2023.1060257 Frontiers in Psychology 10 frontiersin.org courses (Tang et al, 2018;Wang et al, 2018), and students are more proficient in physical skills with flipped classroom teaching in college sports (Zhao, 2022). Moreover, flipped classroom teaching in college sports basketball classes can improve students' professional basketball skills, which is consistent with the results of this study (Wang, 2021).…”
Section: Discussionsupporting
confidence: 83%
“…The “MOOC+ flipped classroom” helped improve students’ basketball skill level and was better than traditional teaching. Related studies have shown that “MOOC+ flipped classroom” teaching can help improve students’ performance in practical courses ( Tang et al, 2018 ; Wang et al, 2018 ), and students are more proficient in physical skills with flipped classroom teaching in college sports ( Zhao, 2022 ). Moreover, flipped classroom teaching in college sports basketball classes can improve students’ professional basketball skills, which is consistent with the results of this study ( Wang, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The creation and Implementation of an Intelligent Assessment System for Physical and Aesthetic Education are essential to enhance personalized learning, optimize curriculum design, identify learning patterns, allocate resources efficiently, monitor health and fitness, promote inclusivity, ensure accountability, engage stakeholders, facilitate continuous improvement, and prepare students for future opportunities [1]. By harnessing data-driven insights, this system enables educators to tailor their approaches, address disparities, and create a more effective and inclusive learning environment, contributing to the holistic development of students in the realms of physical and aesthetic education [2].…”
Section: Introductionmentioning
confidence: 99%
“…Wireless Communications and Mobile Computing has retracted the article titled "College Physical Education Flipped Classroom Teaching Based on Multimedia Network Data Fusion" [1] due to concerns that the peer review process has been compromised.…”
mentioning
confidence: 99%